2000
DOI: 10.1152/jn.2000.83.4.2260
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reversible Inactivation of the Primate Mesencephalic Reticular Formation. I. Hypermetric Goal-Directed Saccades

Abstract: Single-neuron recording and electrical microstimulation suggest three roles for the mesencephalic reticular formation (MRF) in oculomotor control: 1) saccade triggering, 2) computation of the horizontal component of saccade amplitude (a feed-forward function), and 3) feedback of an eye velocity signal from the paramedian zone of the pontine reticular formation (PPRF) to higher structures. These ideas were tested using reversible inactivation of the MRF with pressure microinjection of muscimol, a GABA(A) agonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 72 publications
(136 reference statements)
6
51
2
Order By: Relevance
“…Finally, the three-dimensional range, although shifted torsionally, retained its characteristic "Fick shape", although with a reduced twist. Similar findings were reported previously during INC inactivation in the cat (Fukushima et al 1985a) and similar contralateral head tilts were observed after reversible inactivation of the rostral mesencephalic reticular formation (MRF) in the primate (Waitzman et al 2000b), which lies adjacent to the INC. This raises the question of whether some of the head tilt observed in our experiments was attributable to spread of muscimol to the MRF.…”
Section: Postural Deficits After Inc Inactivationsupporting
confidence: 88%
See 2 more Smart Citations
“…Finally, the three-dimensional range, although shifted torsionally, retained its characteristic "Fick shape", although with a reduced twist. Similar findings were reported previously during INC inactivation in the cat (Fukushima et al 1985a) and similar contralateral head tilts were observed after reversible inactivation of the rostral mesencephalic reticular formation (MRF) in the primate (Waitzman et al 2000b), which lies adjacent to the INC. This raises the question of whether some of the head tilt observed in our experiments was attributable to spread of muscimol to the MRF.…”
Section: Postural Deficits After Inc Inactivationsupporting
confidence: 88%
“…Instead, the eye usually rotated in the same direction as the head. This differs from the compensatory eye position shifts observed during ipsiversive head tilts produced by inactivation of the MRF (Waitzman et al 2000a), suggesting that the latter head tilts may have resulted from an imbalance of input to the INC (integrator) without disrupting the INC itself.…”
Section: Role Of the Inc In Vestibuloocular Functioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Typically the injections at different depths were deeper within the SC, and they were most likely confined within the SC because the observed gaze shift impairments were comparable to previously reported head-restrained saccade deficits (e.g., Lee et al 1988). Also inspection of the animal from a camera revealed no visually detectable signs of tilt in head posture, which has been reported to occur after inactivation of the oculomotor regions of the underlying mesencephalic reticular formation (Farshadmanesh et al 2007;Klier et al 2002;Waitzman et al 2000). In all, 45 lidocaine injections were made in 18 electrode penetrations.…”
Section: Injectionssupporting
confidence: 77%
“…Inactivation of the SC has also been demonstrated to produce deficits in nonsaccadic eye movements, such as smooth pursuit (Basso et al 2000) but, to our knowledge, there are no detailed published data regarding the effects of reversible SC inactivation on gaze shifts in head-unrestrained monkeys. It is known, however, that inactivation of structures downstream of the SC, particularly regions of the mesencephalic reticular formation (Farshadmanesh et al 2007;Klier et al 2002;Waitzman et al 2000), produce severe deficits in head posture. In the present study, reversible inactivation was used to investigate the role of the primate SC in the control of head movements, including not only those that assist in redirecting gaze but also those that occur in the absence of a change in gaze (i.e., vestibuloocular reflex gain equals 1).…”
Section: Introductionmentioning
confidence: 99%